Outcome predictors for maternal red blood cell alloimmunisation with anti‐K and anti‐D managed with intrauterine blood transfusion. (4th December 2021) - Vlachodimitropoulou, Evangelia; Garbowski, Maciej; Anne Solomon, Shelley; Abbasi, Nimrah; Seaward, Gareth; Windrim, Rory; Keunen, Johannes; Kelly, Edmond; Van Mieghem, Tim; Shehata, Nadine; Ryan, Greg
Summary: Red blood cell (RBC) alloimmunisation with anti‐D and anti‐K comprise the majority of cases of fetal haemolytic disease requiring intrauterine red cell transfusion (IUT). Few studies have investigated which haematological parameters can predict adverse fetal or neonatal outcomes. The aim of the present study was to identify predictors of adverse outcome, including preterm birth, intrauterine fetal demise (IUFD), neonatal death (NND) and/or neonatal transfusion. We reviewed the records of all pregnancies alloimmunised with anti‐K and anti‐D, requiring IUT over 27 years at a quaternary fetal centre. We reviewed data for 128 pregnancies in 116 women undergoing 425 IUTs. The median gestational age (GA) at first IUT was significantly earlier for anti‐K than for anti‐D (24·3 vs. 28·7 weeks, P  = 0·004). Women with anti‐K required more IUTs than women with anti‐D (3·84 vs. 3·12 mean IUTs, P  = 0·036) and the fetal haemoglobin (Hb) at first IUT was significantly lower (51.0 vs. 70.5 g/l, P  = 0·001). The mean estimated daily decrease in Hb did not differ between the two groups. A greater number of IUTs and a slower daily decrease in Hb (g/l/day) between first and second IUTs were predictive of a longer period in utero . Earlier GA at first IUT and a shorter interval from the first IUT until delivery predicted IUFD/NND. Earlier GA and lower Hb at first IUT significantly predicted need for phototherapy and/or blood product use in the neonate. In the anti‐K group, a greater number of IUTs was required in women with a higher titre. Furthermore, the higher the titre, the earlier the GA at which an IUT was required in both groups. The rate of fall in fetal Hb between IUTs decreased, as the number of transfusions increased. Our present study identified pregnancies at considerable risk of an unfavourable outcome with anti‐D and anti‐K RBC alloimmunisation. Identifying such patients can guide pregnancy management, facilitates patient counselling, and can optimise resource use. Prospective studies can also incorporate these characteristics, in addition to laboratory markers, to further identify and improve the outcomes of these pregnancies.